Shifting tides: 120 years of migratory flows between Italy and Tunisia - Francesca Fauri (The Journal of European Economic History (JEEH), 2021)
Historically, Mediterranean Africa has been a natural destination for emigrant Italian workers. Between 1900 and 1914, Tunisia was the main destination for Italians emigrating to Africa. Many Sicilian workers, accompanied by their families, settled there, buying small plots of land and thereby changing their status from temporary immigrants to permanent residents. By the late 1920s, nearly 100,000 Italians were living in Tunisia. Between 1940 and 1965, however, first the French colonial authorities and then, after Tunisia become independent on 8 May 1956, the Tunisian government expelled those Italian immigrants. When land confiscation became effective in 1964, Italian settlers returned to Italy for good with the help of Italy's programme for refugees. In June 1965, Italy passed a law indemnifying them for 50 per cent of the value of the farms they had lost in Tunisia. Attempts to obtain compensation from the Tunisian government proved frustrating for Italian refugees, and in the end the Italian government struck a deal whereby Italy offered development aid and took Tunisian wine imports in exchange for compensation for land confiscation. The migratory tide turned rapidly thereafter. From the 1980s onwards, temporary immigrants from Tunisia became indispensable to the "greenhouse district" of southeastern Sicily and to the building sector in Italy's northern regions. This paper will examine the economic motives and impacts of these migratory flows, and the respective governments' reaction to them. In the face of growing immigration from Tunisia, Italy has recently increased economic aid and investment in order to create jobs for young Tunisians at home and reduce the stream of migrants heading for Italy's coasts. In both the earlier departure of Italians for Tunisia and the more recent arrival of Tunisians in Italy, migration Historically, Mediterranean Africa has been a natural destination for emigrant Italian workers. Between 1900 and 1914, Tunisia was the main destination for Italians emigrating to Africa. Many Sicilian workers, accompanied by their families, settled there, buying small plots of land and thereby changing their status from temporary immigrants to permanent residents. By the late 1920s, nearly 100,000 Italians were living in Tunisia. Between 1940 and 1965, however, first the French colonial authorities and then, after Tunisia become independent on 8 May 1956, the Tunisian government expelled those Italian immigrants. When land confiscation became effective in 1964, Italian settlers returned to Italy for good with the help of Italy's programme for refugees. In June 1965, Italy passed a law indemnifying them for 50 per cent of the value of the farms they had lost in Tunisia. Attempts to obtain compensation from the Tunisian government proved frustrating for Italian refugees, and in the end the Italian government struck a deal whereby Italy offered development aid and took Tunisian wine imports in exchange for compensation for land confiscation. The migratory tide turned rapidly thereafter. From the 1980s onwards, temporary immigrants from Tunisia became indispensable to the "greenhouse district" of southeastern Sicily and to the building sector in Italy's northern regions. This paper will examine the economic motives and impacts of these migratory flows, and the respective governments' reaction to them. In the face of growing immigration from Tunisia, Italy has recently increased economic aid and investment in order to create jobs for young Tunisians at home and reduce the stream of migrants heading for Italy's coasts. In both the earlier departure of Italians for Tunisia and the more recent arrival of Tunisians in Italy, migration has temporarily alleviated poverty and economic hardship for individuals. Realistically, however, it is not a politically viable long-run solution.
Keywords: 330